In Defense of the New Hume: A Response to Zuzana Parusniková - Hill, James (Teorie vědy / Theory of Science, 2013)
This article recommends the sceptical realist, or New Hume, interpretation of Hume's theory of causation, in spite of Zuzana Parusniková's critique. However, the author, in line with his developmental interpretation, defends the New Hume only for the Scottish philoso- pher's mature philosophy.